Analysis of the Effect of Promotion and Price on Buying Interest in Yummy Choice Coffee Gold at Indomaret - Wahid, Cecep Abdul; Isyanto, Puji; Sumarni, Neni (Westscience Press, 2025)
Business is currently growing rapidly, as evidenced by the emergence of new business opportunities and challenges faced by every business in the food and beverage sector. Yummy Choice Coffee Gold is the first ready-to-drink product developed by Yummy Choice with a 'Made to Order' concept that serves fresh quality coffee. One of the Yummy Choice Coffee Gold outlets at Indomaret Lingkar Tanjung Pura opened in August 2024. During the grand opening, there was a 20% discount, which greatly attracted consumers to purchase the product. The function of promotion is to serve as an effort to notify or offer products, while price is an important aspect of marketing that is often considered a key factor by consumers when making purchases. This research aims to determine the extent of the influence of promotion and price on purchase interest in Yummy Choice Coffee Gold products at Indomaret, The type of research used is quantitative verificative research. The population is consumers who have shopped at Indomaret, while the sample studied was taken using Hair's formula with 95 respondents. Data was collected through observation and the distribution of questionnaires. The results of this study indicate that there is a positive and significant influence of promotion and price on purchase interest simultaneously for the Yummy Choice Coffee Gold product at Indomaret, and there is a positive and significant influence of promotion and price on purchase interest partially for the Yummy Choice Coffee Gold product at Indomaret.